The Effect of Foliar Spraying with The Nano Fertilizer Optimus-plus on The Growth and Yield of Four Varieties of Kohlrabi - Nashwan Abdulhameed Abbas Al-Baghdadi; Aziz M. A. Shammari (Nabatia, 2024)
The field experiment was carried out in the fall season of the 2019 agricultural season in the fields of the Department of Horticulture and Landscape Engineering, College of Agriculture, University of Diyala, to study the effect of foliar spraying with the Nano fertilizer Optimus-plus at three levels (0, 1.0, 2.0 ml L-1) on the characteristics of vegetative growth and yield of four varieties of Kohlrabi are (local variety, White Vienna, Purple delicacy, Green delicacy) according to the split-plot system, with a completely random block design with three replicates. The results showed that the characteristics of plant height, leaf length, chlorophyll content in the leaves, and the length and weight of the enlarged stem distinguished the Purple Delicacy variety. At the same time, the local variety gave the largest number of leaves, the largest leaf width, the highest length and diameter of the root, and the largest fresh weight of the plant. The White Vienna variety is distinguished by the largest leaf area of the plant, the best diameter, size and weight of the enlarged stem, and the highest total yield. The two foliar spray treatments of 1.0 and 2.0 ml L-1 of the Optimus-plus Nano preparation excelled without significant differences between them in all vegetative growth and yield characteristics compared to the comparison treatment.